A therapeutic vaccine strategy to prevent Pneumocystis pneumonia in an immunocompromised host in a non-human primate model of HIV and Pneumocystis co-infection - Rabacal, Whitney; Schweitzer, Finja; Kling, Heather M.; Buzzelli, Lizabeth; Rayens, Emily; Norris, Karen A. (Frontiers in Immunology, 2022)
Pneumocystis is a ubiquitous fungal pathogen that causes pneumonia (PCP) and pulmonary sequelae in HIV-infected individuals and other immunocompromised populations. With the success of anti-retroviral therapy for HIV-infected individuals the frequency of PCP in that population has decreased, however, PCP remains a significant cause of morbidity and mortality in individuals with hematologic and solid malignancies, and in individuals treated with immunosuppressive therapies for autoimmune diseases, and following bone marrow and solid organ transplantation. Despite the clinical need, there is no approved vaccine to prevent PCP in vulnerable populations. The ultimate goal of the field is to develop an effective vaccine that can overcome immune deficits in at risk populations and induce long-lasting protective immunity to Pneumocystis. Toward this goal, our laboratory has established a model of PCP co-infection in simian immunodeficiency virus (SIV)-infected non-human primates (NHP) and identified a recombinant protein sub-unit vaccine, KEX1, that induces robust anti-Pneumocystis immunity in immune-competent macaques that is durable and prevents PCP following simian immunodeficiency virus (SIV)-induced immunosuppression. Type I, or invariant natural killer T (iNKT) cells have the potential to provide B cell help under conditions of reduced CD4+ T cell help. In the present study, we used the SIV model of HIV infection to address whether therapeutic vaccination with the iNKT cell-activating adjuvant α-galactosylceramide (α-GC) and KEX1 (α-GC+KEX1) can effectively boost anti-Pneumocystis humoral immunity following virus-induced immunosuppression. Immunization of antigen-experienced NHPs with α-GC+KEX1 during the early chronic phase of SIV-infection significantly boosted anti-Pneumocystis humoral immunity by increasing memory B cells and antibody titers, and enhanced titer durability during SIV-induced immunosuppression. This therapeutic vaccination strategy boosted anti-Pneumocystis immune responses during SIV-infection and contributed to protection against Pneumocystis co-infection in KEX1-vaccinated macaques. These studies present a novel strategy for stimulating durable anti-Pneumocystis humoral immunity in the context of complex, chronic SIV-induced immunosuppression and may be further applied to immunization of other immunosuppressed populations, and toward other common recall antigens.